The protective role of algae (Spirulina platensis) and garlic (Allium Sativum), and their combination on alleviation of heat stress in broiler chicken - Hassan, Reda; Hassan, Ebtehal; Abou-shehema, Bahaa; Abu El-Hassan, Sayed; El-Gbaly, Mahmoud; Assar, Mohamed; Morsy, Shama; Zayed , Sherif; Gorgy, Micheal (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
The goal of the current study was to determine the effects of dietary Spirulina and/or garlic powder addition on broiler growth performance, oxidative state, carcass characteristics, blood hematological, and metabolites profile. 600 Ross-308 broiler chicks that were one-day old in total were enlisted. Heat stresses were created starting from day 22 to 35 of age, birds were randomly divided into five treatment groups with 5 replicates × 20 birds per each, where the first one was provided with the basal diet and reared under normal thermal conditions (26 ± 1◦C) to serve as a negative control. Meanwhile, the other four groups were exposed to cyclic heat stress (35 ± 1◦C for 9 h per day) and were fed a basal diet no supplementation to serve as a positive control, positive control diet with 1 gm Spirulina (SP), 200mg garlic powder (GP) and 1g SP+200mg GP respectively. The findings demonstrated that supplementing broilers under heat stress with spirulina and/or garlic powder was effective in reducing the effects of heat stress on growth performance. Additionally, supplementing with spirulina and/or garlic powder had a substantial impact on blood lipid metabolites, as seen by lower levels of serum cholesterol and low-density lipoprotein (LDL) and higher levels of high-density lipoprotein (HDL) lipids. With the addition of Spirulina and/or garlic powder to the heat-stressed group, the amount of lipid peroxidation (MDA) was decreased (p < 0.05), while the antioxidant enzyme activity (TAC) was elevated. Supplementing with 1g of spirulina and/or 200mg of garlic powder increased the proportion of carcass dressing. It can be concluded that feeding broiler chickens supplemented with 1 g of spirulina or 200 mg of garlic powder while they are being raised under heat stress will significantly improve their performance and oxidative state. The best results were seen in the hens fed spirulina with GP.